Organoid: Next-Generation Modeling of Cancer Research and Drug Development - Liu, Jungang; Huang, Xiaoliang; Huang, Lihaoyun; Huang, Jinlian; Liang, Dingyu; Liao, Lixian; Deng, Yuqing; Zhang, Lihua; Zhang, Beibei; Tang, Weizhong (Frontiers in Oncology, 2022)
Colorectal carcinoma is a highly prevalent and heterogeneous gastrointestinal malignancy. The emergence of organoid technology has provided a new direction for colorectal cancer research. As a novel type model, organoid has significant advantages compared with conventional tumor research models, characterized with the high success rate of construction and the high matching with the original tumor. These characteristics provide new possibilities to study the mechanism of colorectal carcinogenesis and improve the treatment effects. The present literature would mainly summarize the characteristics of tumor organoids and the up-to-date technique development of patient-derived organoids (PDOs) and application in colorectal cancer.